CITRA DAKWAH DALAM LIRIK PUISI ENDOI: FEATURES OF ‘DAKWAH’ IN ‘ENDOI’ LULLABIES - Abu Kassim, Noor Sarah; Zakaria, Norazimah (Jurnal Pengajian Melayu (JOMAS), 2020)
The word ‘endoi’ or ‘buai’ in the Malay language describes the act of swinging a cradle gently whilst singing lullabies. However, ‘endoi’ may also refer to the verbal ritual conducted by a Malay family to welcome the birth of a newborn. ‘Endoi’ is a Malay art form believed to contain features of ‘dakwah’ propagating Islamic teachings. This particular form of traditional Malay poetry has lyrics that are suitable for educating the young and spreading ‘dakwah’ within the community. Therefore, this study is defined by two objectives – identifying ‘endoi’ lyrics that contain the features of ‘dakwah’ and discussing their purpose as a ‘dakwah’ medium for the Malays. To achieve these objectives, the study employed the ‘Dakwah Bil Lisan’ methodology based on the ‘dakwah’ method conceptualised by famed religious figure Yusuf Al-Qardhawi. ‘Dakwah Bil Lisan’ is a unique technique or method in which the features ‘dakwah’ can be identified through the characteristics of the speaker at the time of its occurrence. Results showed that ‘dakwah’ is indeed present within ‘endoi’ lyrics based on the three components of Islam: faith (akidah), jurisprudence (syariah) and morals (akhlak). The lyrics were also found to be in line with the two core beliefs in Islam, which are the six pillars of faith or ‘Rukun Iman’ and the five tenets of Islam or ‘Rukun Islam’. It can be concluded that the ‘endoi’ ritual can be practised amongst Malays as it contains features of ‘akidah’, ‘syariah’ and ‘akhlak’ crucial to the upbringing of a true Muslim. Keywords: Traditional Poetry, Culture, Art, Endoi, Dakwah, Dakwah Methods.